Framing Sustainable Healthcare Services - Engelseth, Per (Int J Environ Res Public Health, 2021)
This paper develops an analytical framework using process thinking to achieve sustainable healthcare services. Healthcare is characterised by low economic efficiency. At the same time, it is embedded in ethical concerns related to society and nature. Healthcare is thus conceptualised as functionality in an ecosystem. The patient is woven into both nature and society. Given the complex nature of healthcare services, we seek an alternative way to understand healthcare services, focusing on the exchange aspect of the economy. We offer a conceptual model that helps build an analytical framework focusing on how practitioners and leaders in healthcare frame their activities. This framing provides guidance in healthcare practice. Furthermore, framing is associated with both healthcare service providers as well as patients and next of kin—the recipients. This framework aims to guide practical research and development activities in healthcare.